The Concept of The Mahdi Priest by Shiah: Study on The Interpretation of The Shiah Imamiyah - Haqqy, Ahmad Muzayyan (MAGHZA: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
The concept of Imam Mahdi is a concept of a character who will appear at the end of time and is awaited by his people. In the discussion of Imam Mahdi in the Shia Imamiyah, it is explained that what is meant as Imam Mahdi is Imam Hasan al-Askari, namely the last Imam of the Shia Imamiyah who in his childhood disappeared and is believed to appear as Imam Mahdi at the end of time. The concept of Imam Mahdi has similarities and differences with the concept of Imam Mahdi in Ahlussunnah, Messiah in Judaism, and Jesus in Christianity. The similarity is that all will emerge at the end of time to strengthen each other's religions, while the difference is the character that each concept means is different. The Shia Imamiyah teachings explain that Imam Mahdi will act as 1) Heir and World Leader as described in Surah al-Qashash verses 5-6. 2) Reinforcement of Religion at the End of Time is found in Surah al-Nur verse 55 and Surah al-Taubah verse 33.3) Witnesses for its people are found in Surah al-Nisa verse 41, Surah al-Nahl verses 84 and 89, and Surah al- Qashash verse 75.